1. Section 1.3 - Problem 4 We see that 1 1·2 = 1 2 and 1 1·2 + 1 2·3 = n X k=1 2 3 and 1 1·2 + 1 2·3 + 1 3·4 = 3 4 and conjecture that 1 n = k(k + 1) n+1 This is true for the base case, where n = 1, as shown above. For the inductive step we assume the conjecture is true for n and prove for n + 1. n+1 X k=1 n X 1 1 1 = + k(k + 1) k=1 k(k + 1) (n + 1)(n + 2) 1 n + , by the induction assumption n + 1 (n + 1)(n + 2) n(n + 2) + 1 = (n + 1)(n + 2) n2 + 2n + 1 = (n + 1)(n + 2) (n + 1)2 = (n + 1)(n + 2) n+1 . = n+2 P 1 n Thus by induction we have nk=1 k(k+1) = n+1 for all n ∈ Z, n ≥ 1. = 2. Section 1.3 - Problem 8 P The base case is 1k=1 j 3 = 1 = [1(1 + 1)/2]2 , so the result holds for n = 1. For the inductive step we prove the result is true for n + 1 if we assume the result is true for n. We have n n+1 X X j 3 + (n + 1)3 j3 = k=1 k=1 = [n(n + 1)/2]2 + (n + 1)3 , by the induction assumption n2 + n + 1) 4 n2 + 4n + 4 = (n + 1)2 4 2 2 (n + 2) = (n + 1) 4 2 (n + 1)(n + 2) = . 2 P Thus by induction we have nk=1 j 3 = [n(n + 1)/2]2 for all n ∈ Z, n ≥ 1. = (n + 1)2 ( 3. Section 1.3 - Problem 12 P The base case is 1k=1 j · j! = 1 · 1! = 1 = 2! − 1, so the result holds for n = 1. For the inductive step we prove the result is true for n + 1 if we assume the result is true for n. We have n+1 X k=1 j · j! = n X j · j! + (n + 1) · (n + 1)! k=1 = (n + 1)! − 1 + (n + 1) · (n + 1)! , by the induction assumption = (n + 1 + 1) · (n + 1)! − 1 = (n + 2)! − 1 P Thus by induction we have nk=1 j · j! = (n + 1)! − 1 for all n ∈ Z, n ≥ 1. 4. Section 1.3 - Problem 14 The problem here is equivalent to showing that for all integers n ≥ 54, there exist nonnegative integers a and b such that n = 7a + 10b. Method 1 The base case is shown to be true, as illustrated by 54 = 7 · 2 + 10 · 4. For the inductive step we assume that the result is true for some n ≥ 54, and we prove the result for n + 1. By the inductive assumption we can write n = 7a + 10b. Suppose b ≥ 2. Then as 21 = 3 · 7 = 2 · 10 + 1, we have n + 1 = 7(a + 3) + 10(b − 2) Otherwise we have b ≤ 1. As n = 7a + 10b ≥ 54, we thus have 7a ≥ n − 10 ≥ 44 and so a ≥ 7. As 50 = 5 · 10 = 7 · 7 + 1 we then have n + 1 = 7(a − 7) + 10(b + 5) In both cases we can write n + 1 = 7c + 10d for some non-negative integers c and d. Thus by induction our result holds for all n ≥ 54. Method 2 An alternative approach uses strong induction. We first show that the result holds for the following integers: 54 = 7 · 2 + 10 · 4 55 = 7 · 5 + 10 · 2 56 = 7 · 8 + 10 · 0 57 = 7 · 1 + 10 · 5 58 = 7 · 4 + 10 · 3 59 = 7 · 7 + 10 · 1 60 = 7 · 0 + 10 · 6 For the inductive step, let n ≥ 60 and assume the result holds for all k such that 54 ≤ k ≤ n. We prove the result holds for n + 1. As n ≥ 60 we have n − 6 ≥ 54, and by the inductive assumption we can write n − 6 = 7a + 10b. Then n + 1 = 7(a + 1) + 10b. Thus by strong induction our result holds for all n ≥ 54. 5. Section 1.3 - Problem 22 For the base case the inequality becomes 1 + 0h = 1 = (1 + h)0 , which is true, so the result holds for n = 0. For the inductive step we prove the result is true for n + 1 if we assume the result is true for n. We have (1 + h)n+1 = (1 + h)n (1 + h) ≥ (1 + nh)(1 + h) , by the induction assumption, and as 1 + h ≥ 0 = 1 + h + nh + nh2 ≥ 1 + h + nh = 1 + (n + 1)h. Thus by induction we have 1 + nh ≤ (1 + h)n for all n ∈ Z, n ≥ 0. 6. Section 1.3 - Problem 24 The proof fails in the induction argument. It reasons that the sets {1, . . . , n} and {2, . . . , n + 1} will have common members. This is false when n + 1 = 2. In this case the sets are {1} and {2}, which are disjoint, and the argument breaks down. 7. Section 1.3 - Problem 34 The base step here is clear. In a 2 × 2 chessboard with one square missing, the 3 other squares form an L-shaped piece. Assume that any 2n × 2n chessboard with one square missing can be filled by L-shaped pieces, and consider a 2n+1 × 2n+1 chessboard with an arbitrary square missing. This 2n+1 × 2n+1 chessboard consists of 4 2n × 2n chessboard arranged in a square. Exactly one of these smaller chessboards will be missing one square, so by the inductive assumption, this smaller chessboard can be covered using L-shaped pieces. The other 3 smaller chessboards have no squares missing. Place one L-shaped piece in the center of the larger piece, so that 1 square of this L-shaped piece lies in each of these 3 smaller chessboards. Now each of these 3 smaller chessboards need to have all of their pieces except this 1 at the center covered by L-shaped pieces. By the inductive assumption, this is possible. Hence by induction, any 2n × 2n chessboard with one square missing can be covered by L-shaped pieces. 8. Section 3.1 - Problem 2 The numbers (a) 201 = 3 · 67, (b) 203 = 7 · 29, (c) 207 = 3 · 69, (e) 213 = 3 · 71, and (f) 221 = 13 · 17 are all composite. The only prime√is (d) 211. This can be seen by checking that 211 is not divisible by any of the primes p ≤ 203 < 15, i.e., by p = 2, 3, 5, 7, 11 and 13. 9. Section 3.1 - Problem 6 We factor n3 + 1 = (n + 1)(n2 − n + 1). Suppose n3 + 1 is prime. Then n3 + 1 > 1 and so n > 0. Hence n + 1 > 1 and so by the factoring above we require n + 1 = n3 + 1. This equality holds if and only if n = 1, in which case the number is 13 + 1 = 2. In conclusion, no integer of the form n3 + 1 is prime, other then 2 = 13 + 1. 10. Section 3.1 - Problem 8 As Qn = n! + 1 > 1, there exists a prime p dividing Qn . Suppose p ≤ n. Then p divides n! and therefore p divides Qn − n! = 1, which is impossible. Thus p > n. Suppose there are finitely many primes. Then there exists a largest prime n. But by the above argument, there exists a prime p > n dividing n! + 1. This is a contradiction and thus there are infinitely many primes.